First experience with the new generation Edwards Sapien 3 aortic bioprosthesis: procedural results and short term outcome - Murray, Marie-Isabel; Geis, Nicolas; Pleger, Sven Torsten; Kallenbach, Klaus; Katus, Hugo; Bekeredjian, Raffi; Chorianopoulos, Emmanuel (Journal of interventional cardiology, 2015)
Background TAVR has become an established treatment for severe symptomatic aortic stenosis in patients with high surgical risk. The latest generation of the balloon-expandable Edwards Sapien device, the Sapien 3, together with its new transfemoral Commander delivery system has been designed to reduce paravalvular regurgitation and vascular access site complications. Objectives To evaluate procedural results and short term outcome with the third generation Sapien 3 device. Methods We retrospectively evaluated 125 consecutive TAVR patients and analyzed the first 51 patients in whom we implanted the new Sapien 3 device via transfemoral access. Results In patients implanted with the Sapien 3 device significant residual paravalvular regurgitation after TAVR was virtually absent with the vast majority having none or trace postinterventional aortic regurgitation on angiography or echocardiography (92.2% and 80.4% respectively). None of the patients had more than mild paravalvular regurgitation. Major vascular access site complications or major bleeding according to the VARC II criteria were not observed in our cohort, minor vascular complications and minor bleeding occurred in 7.8% and 5.9% respectively. If vascular complications occurred, they were related to closure device failure. Thirty day outcome showed a 1.9% major stroke rate and 3.9% death rate. However, we observed a 25.5% permanent pacemaker rate in our Sapien 3 cohort. Conclusions Implantation of the new third generation Sapien 3 device resulted in excellent procedural and short term outcome. Significant paravalvular regurgitation was virtually absent. However, the increased rate of postinterventional pacemaker implantations needs to be analyzed in a larger cohort of patients. (J Interven Cardiol 2015;28:109-116)
Gesehen am 03.07.2017